2020
DOI: 10.1021/acsami.0c08873
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Multilayer versus Monolayer Dodecanethiol on Selectivity and Pattern Integrity in Area-Selective Atomic Layer Deposition

Abstract: Monolayer and multilayer dodecanethiols (DDT) can be assembled onto a copper surface from the vapor phase depending on the initial oxidation state of the copper. The ability of the copper-bound dodecanethiolates to block atomic layer deposition (ALD) and the resulting behavior at the interfaces of Cu/SiO2 patterns during area-selective ALD (AS-ALD) are compared between mono- and multilayers. We show that multilayer DDT is ∼7 times more effective at blocking ZnO ALD from diethylzinc and water than is monolayer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 54 publications
7
38
0
Order By: Relevance
“…In fact, its surface morphology is much closer to that of a multilayer DDT-coated Cu sample (Figure S3, Supporting Information), which was fabricated by exposing DDT vapor onto a CuO-covered Cu substrate. [30,34] These AFM results correlate well with the interpretation of the XPS results in Figure 1c that a monolayer DDT structure can still be maintained with slight Cu oxidation, whereas a multilayer DDT structure starts to form as the oxidation time increases significantly. XPS high-resolution scans were performed on blanket acetic acid-etched Cu substrates with different oxidation times to better understand how the surface oxidation state of Cu changes during the oxidation and how that affects DDT quality.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…In fact, its surface morphology is much closer to that of a multilayer DDT-coated Cu sample (Figure S3, Supporting Information), which was fabricated by exposing DDT vapor onto a CuO-covered Cu substrate. [30,34] These AFM results correlate well with the interpretation of the XPS results in Figure 1c that a monolayer DDT structure can still be maintained with slight Cu oxidation, whereas a multilayer DDT structure starts to form as the oxidation time increases significantly. XPS high-resolution scans were performed on blanket acetic acid-etched Cu substrates with different oxidation times to better understand how the surface oxidation state of Cu changes during the oxidation and how that affects DDT quality.…”
Section: Resultssupporting
confidence: 84%
“…[28] However, previous results have shown that it is challenging to obtain good selectivity in AS-ALD of Al 2 O 3 . [23,29,30] Therefore, developing a more robust alkanethiol SAM inhibitor that is more effective for Al 2 O 3 ALD is essential.In this work, we demonstrate an approach to improve the packing of dodecanethiol (DDT) SAMs by applying an additional oxidation process on acid-etched Cu surfaces prior to DDT deposition. We follow the oxidation process, observing that Cu 2 O forms first followed by CuO, and show that the different oxide compositions at the Cu substrates influence the subsequent DDT formation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The degradation of the ODPA SAM is attributed to the presence of HCl, a byproduct for the SiOC MLD process (Figure ), which can readily attack the surface CuO x and destroy the ODPA binding to the CuO x . Alternatively, we tested DDT SAMs on Cu pretreated with acetic acid, which may be more suitable because in this system, DDT molecules bind directly to metallic Cu atoms. ,,, Therefore, the degradation of the DDT SAM can be avoided because no etchable oxidized Cu layer exists. After SiOC deposition on both Cu and DDT-Cu, XPS spectra were collected.…”
Section: Resultsmentioning
confidence: 99%
“…DDT SAMs were deposited on Cu substrates by vapor phase deposition. In order to form a monolayer DDT SAM, the surface oxides on Cu were removed by soaking the Cu substrates in glacial acetic acid for 2 min, as described in our previous reports. , After N 2 drying, Cu substrates were placed in a vacuum chamber with pressure lower than 10 mTorr. A DDT-containing bubbler was preheated to 65 °C.…”
Section: Methodsmentioning
confidence: 99%